Productive and Reproductive Performance of Different Crossbred Cattle at Sylhet Govt. Dairy Farm (Progressive Agriculture, 2013)
The study was conducted at Sylhet Govt. dairy farm to evaluate the productive and reproductive performance of Jersey× Frisian (J×F), Jersey × Local (J×L) and Sahiwal × Local (SL×L.) crossbred during the period of April 2007 to August 2009. Data on milk yield and different reproductive traits like lactation length, milk yield, length of dry period, service per conception, gestation length and post-partum heat period were evaluated. Results indicated that milk yield, length of dry period, service per conception and post-partum heat period were significantly affected (P